Behavioral and distributional effects of environmental policy: Introduction - Carlo Carraro; Gilbert E. Metcalf (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper introduces to the main policy research issues that the interrelationship between environmental and economic problems has recently emphasised. Economists have traditionally encouraged the use of incentive-based instruments in place of command and control regulation. The starting point for a discussion on efficient environmental policy has been the Pigouvian prescription: to set taxes on pollution equal to marginal environmental damages. In recent years, however, economists have come to recognise that the standard Pigouvian prescription needs to be modified in the face of other important economic and political considerations. The reasons for this modification of the standard Pigouvian prescription can be found in the nature of the environmental problems to be managed. These problems are often characterised by a transnational dimension, by links to other economic issues, and by their interrelationship with several types of economic externalities. All this implies that environmental policy has to be re-designed in order to be effective even in a world where the policymakers may have multiple interrelated targets and an incomplete set of policy instruments. This introduction is forthcoming in the book "Behavioral and Distributional Effects of Environmental Policy" edited by Carlo Carraro and Gilbert Metcalf. This volume includes ten papers that were prepared as part of a joint research project on environmental policy carried out by the Fondazione Eni Enrico Mattei (FEEM) and the National Bureau of Economic Research (NBER). The papers were presented at a conference hosted by FEEM at their headquarters in Milan, Italy on June 11-12, 1999.
Keywords: L00; H2; Q2; 330; Environmental policy; taxation; incentives; regulation; income distribution; Umweltpolitik; Ökosteuer; Theorie